Factors that may contribute to an inadequate radiology request form - Mitch Otterberg; Johan Gunneröd (Radiography Open, 2019)
The radiology request/referral is an important part of the communication between the referring physician and the radiology department. It forms the basis for radiologists and radiographers to be able to carry out their work. Through the radiologic request form, the referrer orders an examination for a patient, as part of the patient's medical examination or follow-up. In conjunction with education and practice, we have noticed that reduced quality of the referrals is not uncommon. The aim was to identify the main contributing factors to unjustified referrals for diagnostic imaging procedures. A literature review was undertaken.